Kesulitan Belajar Siswa dalam Mata Pelajaran Bahasa Indonesia di Sekolah Dasar - Muh Syawal; Haryadi Haryadi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to describe students’ learning difficulties in the Indonesian language learning process at the Elementary School and to explore the factors that cause learning difficulties Indonesian in Elementary School. This study uses a kualitattive research design with case studies. The subjects in this study were students of Elementary School. The data collection techniques used in this study are Observation and Interview. Analysis techniques using miles and huberman models are reduction, display, and verification. The result of this study is that there are internal and external factors of students in learning Indonesian, especially in students' reading learning materials. The internal factor is the lack of motivation and interest in reading from the student itself, students are still not motivated in following the indonesian language learning process and students' interest in learning Indonesian is still lacking. The external factors are first: the lack of creativity of the teacher in the learning process takes place, so that it makes students saturated and less pleasant in following the learning process Indonesian, then the methods used by teachers are also not varied and less attractive to students. Second: parents' lack of attention and encouragement towards a child's learning achievement, especially in the process of learning to read. Based on the results of observations and interviews conducted in Elementary School it can be concluded that there so many students who are still having difficulties in the process of learning to read. Keywords: Learning Difficulty, Reading Difficulties, Elementary School